2020
DOI: 10.1016/j.ijppaw.2019.11.005
|View full text |Cite
|
Sign up to set email alerts
|

First case of Trichinella spiralis infection in beavers (Castor fiber) in Poland and Europe

Abstract: BackgroundThis is the first report of the finding of Trichinella spiralis in beaver meat (Castor fiber) in Poland and Europe. In Poland, the beaver is a strictly protected animal species, except the few regions where high population density leads to economic losses. In these areas, the reduction culling of the animals was introduced. This uncommon hunting game animal is consumed and treated as a delicacy by hunters. However, currently, there is a lack of knowledge on possible risk factors for humans associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Unfortunately, foodborne parasites remain neglected compared with bacterial and viral pathogens [3]. Therefore, studies in this field, like epidemiological surveys [5,6], development of novel diagnostic tools [7][8][9], drug discovery [10], or investigation of pathogenicity [11], are particularly valuable.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, foodborne parasites remain neglected compared with bacterial and viral pathogens [3]. Therefore, studies in this field, like epidemiological surveys [5,6], development of novel diagnostic tools [7][8][9], drug discovery [10], or investigation of pathogenicity [11], are particularly valuable.…”
Section: Introductionmentioning
confidence: 99%
“…In central Europe, Italy had the most publications, with 10 articles (Badagliacca et al, 2016;Bandino et al, 2015;Marucci et al, 2021;Pozio et al, 2021;Ricchiuti et al, 2021), while in Eastern Europe, Poland had the largest number of studies, a number of which were published recently (Bień et al, 2016;Bilska-Zając et al, 2016, 2017Cybulska et al, 2016Cybulska et al, , 2019Cybulska et al, , 2020Flis et al, 2017;Hurníková et al, 2016;Różycki et al, 2020).…”
Section: Palearctic Regionmentioning
confidence: 99%
“…Protozoon parasites present in European beavers are Cryptosporidium , Giardia (Bystrianska et al 2021 ), and Eimeria (Goodman et al 2012 ) spp. Among endoparasite helminth species, the flatworms Psilotrema castoris , Stichorchis subtriquetrus (Demiaszkiewicz et al 2014 ), Echinococcus multilocularis , Taenia martis (Campbell-Palmer et al 2015 ), Fasciola hepatica (Shimalov and Shimalov VT 2000); the nematode Travassosius rufus (Bystrianska et al 2021 ), Trichostrongylus capricola (Demiaszkiewicz et al 2014 ), Calodium hepaticum (Mészáros and Kemenes 1973 ; Fuehrer 2014 ), Trichinella spiralis (Różycki et al 2020 ) and Trichinella britovi (Seglina et al 2015 ) were found in C. fiber . Among ectoparasites, there are fur mites from the genus Schizocarpus , Demodex follicule mites (Izdebska et al 2016 ); two hard tick species Ixodes hexagonus (Haitlinger 1991 ) and Ixodes apronophorus (Kadulski 1998 ) and a unique epidermal tissue feeding beetle, Platypsyllus castoris (Åhlen et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%